2022
DOI: 10.3389/fpubh.2022.1076090
|View full text |Cite
|
Sign up to set email alerts
|

Visiting crowded places during the COVID-19 pandemic. A panel study among adult Norwegians

Abstract: Non-pharmaceutical interventions, including promotion of social distancing, have been applied extensively in managing the COVID-19 pandemic. Understanding cognitive and psychological factors regulating precautionary behavior is important for future management. The present study examines the importance of selected factors as predictors of having visited or intended to visit crowded places. Six online questionnaire-based waves of data collection were conducted in April–October 2020 in a Norwegian panel (≥18 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Evidence about people’s willingness to visit public places during the COVID-19 pandemic indicates that the necessity of the activity may intersect with people’s personal risk assessment and tolerance. Surveys of people’s willingness to engage in various activities found that grocery shopping was the most frequently engaged in activity [ 9 , 47 ] and a principal component analysis suggested that engagement in this specific activity was fundamentally different for people than other less necessary activities, such as attending large gatherings or indoor dining [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence about people’s willingness to visit public places during the COVID-19 pandemic indicates that the necessity of the activity may intersect with people’s personal risk assessment and tolerance. Surveys of people’s willingness to engage in various activities found that grocery shopping was the most frequently engaged in activity [ 9 , 47 ] and a principal component analysis suggested that engagement in this specific activity was fundamentally different for people than other less necessary activities, such as attending large gatherings or indoor dining [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire included detailed questions about their social contacts, exposure to social distancing measures, uptake of preventive measures, and attitudes and risk perception regarding the COVID-19 pandemic. This article focuses on the social contact data and related personal protection measures (hand washing, use of hand sanitiser and face masks) while analyses of other survey topics have been published previously (17, 18) or are planned to be published soon.…”
Section: Methodsmentioning
confidence: 99%
“…Other findings from the Norwegian CoMix survey have underscored the importance of cognitive and psychological factors in predicting behaviour, in particular identifying predictors of visiting or intending to visit crowded places during the study period (18). Furthermore, the information gathered through social surveys can be complemented by research utilising non-standard data sources.…”
Section: Limitationsmentioning
confidence: 99%
“…The questionnaire included detailed questions about their social contacts, exposure to social distancing measures, uptake of preventive measures, and attitudes and risk perception regarding the COVID-19 pandemic. This article focuses on the social contact data and related personal protection measures (hand washing, use of hand sanitiser and face masks) while analyses of other survey topics have been published previously [20,21] or are planned to be published soon.…”
Section: Data Collection and Recruitmentmentioning
confidence: 99%
“…Other findings from the Norwegian CoMix survey have underscored the importance of cognitive and psychological factors in predicting behaviour, in particular identifying predictors of visiting or intending to visit crowded places during the study period [ 21 ]. Furthermore, the information gathered through social surveys can be complemented by research utilising non-standard data sources.…”
Section: Limitationsmentioning
confidence: 99%